Prevalence and antimicrobial resistance profiles of extended-spectrum beta-lactamase-producing Escherichia coli in East Tennessee dairy farms - Gelalcha, Benti D.; Gelgie, Aga E.; Kerro Dego, Oudessa (Frontiers in Veterinary Science, 2023)
The extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae, such as E. coli, are emerging as a serious threat to global health due to their rapid spread and their multidrug-resistant (MDR) phenotypes. However, limited information is available regarding the prevalence and antimicrobial resistance (AMR) profile of ESBL-E. coli in the U.S. dairy farms. This study aimed to determine the prevalence and AMR pattern of ESBL-E. coli in East Tennessee dairy cattle farms. Rectal fecal samples from dairy cattle (n=508) and manure (n=30), water(n=19), and feed samples(n=15) were collected from 14 farms. The presumptive E. coli was isolated on CHROMagar™ ESBL and confirmed by Matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS). From 572 fecal and farm environmental samples, a total of 233 (41%, n=572) ESBL-E. coli were identified. Antimicrobial susceptibility testing was performed on the ESBL-E. coli isolates. The prevalence of fecal ESBL-E. coli was 47.5% (95% CI: 46.2 -49.2). The within-farm prevalence of ESBL-E. coli ranged from 8% to 100%. Recent treatment history with third-generation cephalosporins (3GC), cow parity ≥ 3, and calves were the independent risk factors associated (P<0.05) with fecal carriage of ESBL-E. coli. Overall, 99.6%(n=231) ESBL-E. coli tested were phenotypically resistant to at least one of the 14 antimicrobial agents tested. The most common AMR phenotypes were against beta-lactam antibiotics, ampicillin (99.1%; n=231 isolates), and ceftriaxone (98.7%; n=231). Most ESBL-E. coli isolates (94.4%) were MDR (resistance to ≥ 3 antimicrobial classes), of which 42.6% showed co-resistance to at least six classes of antibiotics. ESBL-E. coli isolates with concurrent resistance to ceftriaxone, ampicillin, streptomycin, tetracycline, sulfisoxazole, and chloramphenicol are widespread and detected in all the farms. The detection of MDR ESBL-E. coli suggests that dairy cattle can be a reservoir for these bacteria, highlighting the associated public health risk..